Yield Behavior of Sand Under Generalized Stress Conditions - O'Kelly, Brendan (My University, 2005)
The yield behavior of Leighton Buzzard sand was studied for different magnitudes of the three principal stresses and different orientations of the major principal stress using a hollow cylinder apparatus. Stress paths were followed that allowed well defined portions of different yield surfaces to be determined under generalized stress conditions. The Matsuoka-Nakai and Lade yield criteria were both found to adequately predict the onset of yielding under generalized stress conditions. The experimental data indicated that the onset of yielding as predicted by both yield criteria was independent of the orientation of the major principal stress and magnitude of the intermediate principal stress.
Poster presentation at the 16th International Conference on Soil Mechanics and Geotechnical Engineering (ICSMGE)
PRESENTED
Osaka, Japan
Keywords: sand